EFEKTIVITAS PENERIMAAN PAJAK BUMI DAN BANGUNAN PADA BAPENDA KABUPATEN BANDUNG (PERIODE 2017-2021) - Rum, Avid Inang; Oktaviana, Siti Rina (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2023)
This final project is entitled Review of the Effectiveness of Land and Building Tax Revenue at Bappenda Bandung Regency (2017-2021 Period). The purpose of this study is to find out how the target, realization, and effectiveness of land and building tax revenue at Bappenda Bandung Regency (2017-2021 Period). The method used in this study uses a descriptive method with a qualitative approach. This research data collection technique was carried out by observation, interviews, and literature study. The data obtained were analyzed by means of data reduction, data presentation, and drawing conclusions. The types and sources of data in this study are target data and realization of land and building tax revenues for the rural and urban sectors for 2017-2021 in Bandung district. The results of the study show that the effectiveness of land and building tax revenue in the rural and urban sectors at the Bandung Regency Regional Revenue Agency for the 2017-2021 period can be said to be quite effective despite fluctuating (up and down). The highest percentage for achieving effectiveness is in 2021, which is 116.08%, and the lowest achievement is in 2020, which is 96.46%.